Contribution of sugarcane crop wild relatives in the creation of improved varieties in Mauritius. Issue 2 (16th January 2019) - Santchurn, D.; Badaloo, M.G.H.; Zhou, M.; Labuschagne, M.T.
Abstract: Significant genetic diversity for sucrose and fibre percentages exists in the species that served as the foundation of present day sugarcane cultivars. However, information is lacking worldwide on the recent contributions of sugarcane crop wild relatives (mainly Saccharum, Erianthus and Miscanthus wild species) in developing new varieties. There is renewed interest in using those relatives for creating new varieties to use as a dedicated bioenergy crop with higher fibre. This study focuses on past data analysis of sugarcane breeding in Mauritius with the objective to assess the efficiency in exploiting sugarcane wild relatives since 1970s to date. Pedigree analyses helped retrace the parentages of elite inter-specific hybrids reaching the final stages of selection. The studies confirmed the high prevalence of a few 'wonder canes' (successful hybrids with wild canes produced in the beginning of last century) among the ancestors of Mauritian varieties. Among the wild relatives, eight Saccharum spontaneum, two S. robustum, and one Erianthus clones were involved in generating elite genotypes worth evaluating at the advanced variety trial stages. A few early generation hybrids were released in the past for industrial exploitation, the latest one being M 1002/02 in 2016, with sugar as the primary output. Recent studies on the biomass potential and fibre yield of inter-specific hybrids are giving promising results, which expands the horizon in the use of sugarcane wild relatives for the generation of novel type of sugarcane varieties for multiple end-uses.